High p‐mTOR expression is associated with recurrence and shorter disease‐free survival in atypical meningiomas. Issue 1 (3rd December 2018) - Barresi, Valeria; Lionti, Simona; La Rocca, Lilli; Caliri, Samuel; Caffo, Maria
Abstract : Due to their widely variable clinical behavior, the post‐surgical treatment of atypical meningiomas is controversial. Therefore, prognostic factors able to identify high‐risk cases, which may benefit from adjuvant treatments, are warranted. Mammalian target of rapamycin (mTOR) belongs to the PI3K‐AKT pathway. Its phosphorylated form (p‐mTOR Ser2448) is involved in cell growth, differentiation and tumorigenesis. The aim of this study was to evaluate p‐mTOR Ser2448 expression and its eventual correlation with clinicopathological features, recurrence, or disease‐free survival (DFS), in atypical meningiomas. p‐mTOR immunohistochemical expression was analyzed in 48 atypical meningiomas and correlated with clinicopathological parameters and with DFS. Eighty‐one percent of atypical meningiomas expressed p‐mTOR Ser2448. High immuno‐expression was significantly associated with recurrences ( P = 0.01) and lower DFS ( P = 0.01). The presence of brain invasion, high mitotic index plus sheeting, and Simpson grade were significant and independent prognostic variables at multivariate analysis. p‐mTOR Ser2448 is expressed in atypical meningiomas. High expression predicts development of recurrences and shorter DFS in patients affected by these tumors. Since p‐mTOR Ser2448 is a target of anti‐neoplastic drugs, evaluation of its expression may be used, not only to identify atypical meningiomas at higher risk of recurrence, but also to select those to submit to adjuvant targeted chemotherapy.